Second-Order Conditioning and Conditioned Inhibition in Different Moments of the Same Training: The Effect of A+ and AX− Trial Number - Muñiz-Diez, Clara; Muñiz-Moreno, Judit; Loy, Ignacio (Frontiers in Behavioral Neuroscience, 2021)
The feature negative discrimination (A+/AX−) can result in X gaining excitatory properties (second-order conditioning, SOC) or in X gaining inhibitory properties (conditioned inhibition, CI), a challenging finding for most current associative learning theories. Research on the variables that modulate which of these phenomena would occur is scarce but has clearly identified the trial number as an important variable. In the set of experiments presented here, the effect of trial number was assessed in a magazine training task with rats as a function of both the conditioning sessions and the number of A+ and AX− trials per session, holding constant the total number of trials per session. The results indicated that SOC is most likely to be found at the beginning of training when there are many A+ and few AX− trials, and CI (as assessed by a retardation test) is most likely to be found at the end of training when there are few A+ and many AX− trials. Both phenomena were also found at different moments of training when the number of A+ trials was equal to the number of AX− trials. These results cannot be predicted by acquisition-focused associative models but can be predicted by theories that distinguish between learning and performance.